2022
DOI: 10.1038/s41598-022-16310-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA-aptamer-nanographene oxide as a targeted bio-theragnostic system in antimicrobial photodynamic therapy against Porphyromonas gingivalis

Abstract: The aim of this study was to design and evaluate the specificity of a targeted bio-theragnostic system based on DNA-aptamer-nanographene oxide (NGO) against Porphyromonas gingivalis during antimicrobial photodynamic therapy (aPDT). Following synthesis and confirmation of NGO, the binding of selected labeled DNA-aptamer to NGO was performed and its hemolytic activity, cytotoxic effect, and release times were evaluated. The specificity of DNA-aptamer-NGO to P. gingivalis was determined. The antimicrobial effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Zinc oxide functionalized graphene oxide polyetheretherketone was reported as an antibacterial agent against periodontal pathogens and biofilms [ 101 , 102 ]. Another study demonstrated that DNA-aptamer-nanographene oxide was highly effective in reducing Porphyromonas gingivalis [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide functionalized graphene oxide polyetheretherketone was reported as an antibacterial agent against periodontal pathogens and biofilms [ 101 , 102 ]. Another study demonstrated that DNA-aptamer-nanographene oxide was highly effective in reducing Porphyromonas gingivalis [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…The DNA-aptamer-NGO presents an intrinsic antibacterial activity and increases under irradiation. Their action mechanism reduces bacterial metabolic activity, as observed in Figure 3b, which leads to a higher rate of bacterial apoptosis as a function of concentration and irradiation (see Figure 3c) [71]. In APDT with GO, there is a dependence between the light dose and the loss of bacterial viability, for example, for the bacteria E. coli, its loss of viability is aggravated for 40-60 J⋅cm −2 at higher concentrations.…”
Section: Graphene Oxide and Reduced-graphene Oxide In Apdtmentioning
confidence: 93%
“…That is, there is a threshold of light dose and concentrations of the PS, where the photons are available to excite GO and generate 1 O 2 and the ROS is optimal for causing bacterial death and avoiding affecting healthy tissues. gingivalis with DNA-aptamer-NGO in APDT [71]. (c) The apoptosis rate of P. gingivalis with DNA-aptamer-NGO in APDT [71].…”
Section: Graphene Oxide and Reduced-graphene Oxide In Apdtmentioning
confidence: 99%
See 2 more Smart Citations